Melanoma brain metastases: interdisciplinary management recommendations 2020 - Gutzmer, Ralf; Vordermark, Dirk; Hassel, Jessica C.; Krex, Dietmar; Schadendorf, Dirk; Sickmann, Thomas; Rieken, Stefan; Pukrop, Tobias; Höller, Christoph; Eigentler, Thomas; Meier, Friedegund (Cancer treatment reviews, 2020)
Melanoma brain metastases (MBM) are common and associated with a particularly poor prognosis; they directly cause death in 60-70% of melanoma patients. In the past, systemic treatments have shown response rates around 5%, whole brain radiation as standard of care has achieved a median overall survival of approximately three months. Recently, the combination of immune checkpoint inhibitors and combinations of MAP-kinase inhibitors both have shown very promising response rates of up to 55% and 58%, respectively, and improved survival. However, current clinical evidence is based on multi-cohort studies only, as prospectively randomized trials have been carried out rarely in MBM, independently whether investigating systemic therapy, radiotherapy or surgical techniques. Here, an interdisciplinary expert team reviewed the outcome of prospectively conducted clinical studies in MBM, identified evidence gaps and provided recommendations for the diagnosis, treatment, outcome evaluation and monitoring of MBM patients. The recommendations refer to four distinct scenarios: patients (i) with ‘brain-only’ disease, (ii) with oligometastatic asymptomatic intra- and extracranial disease, (iii) with multiple asymptomatic metastases, and (iv) with multiple symptomatic MBM or leptomeningeal disease. Changes in current management recommendations comprise the use of immunotherapy - preferably combined anti-CTLA-4/PD-1-immunotherapy - in asymptomatic MBM minus/plus stereotactic radiosurgery which remains the mainstay of local brain therapy being safe and effective. Adjuvant whole-brain radiotherapy provides no clinical benefit in oligometastatic MBM. Among the systemic therapies, combined MAPK-kinase inhibition provides, in BRAFV600-mutated patients with rapidly progressing or/and symptomatic MBM, an alternative to combined immunotherapy.
Gesehen am 16.02.2021